Assessment of different extenders for the cryopreservation of Moroccan Beni Arouss buck semen with no sperm washing - Ouarib A.; Raes M.; Bister J.; Kirschvinck N.; Archa B.; Chentouf M.; El Kadili S. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
This study aimed at investigating the effects of two commercial extenders and skimmed milk extender on the quality of cryopreserved buck semen without washing. Ejaculates were collected from four Beni Arouss bucks using an artificial vagina, pooled and split into equal parts in three tubes. Tubes were diluted in parallel at 37°C with Optixcell® semen extender already containing glycerol, INRA96® semen extender and skim milkbased extender. After cooling to 4°C, glycerol (7%) was added to samples diluted with INRA96® and skimmed milk extenders and all samples were equilibrated, cryopreserved and stored in liquid nitrogen. CASA motion parameters, viability and normal morphology of sperm were assessed after dilution, equilibration and freeze–thawing. The cryopreservation process had a significant effect on semen quality. All parameters decrease over time of the storage process (P < 0.001). Optixcell® extender provided more effective preservation after freeze-thawing followed by skimmed milk extender and then INRA96® extender (P < 0.05) of progressive motility (47%, 35% and 16%, respectively), velocity parameters (RAPID: 48%, 33% and 14% respectively and VCL: 100 μm/s, 83 μm/s, 71 μm/s and VSL: 58 μm/s, 56 μm/s and 45 μm/s, respectively) and viability (41%, 32% and 16%, respectively). No significant differences were observed between extenders regarding the normal morphology (P > 0.05). It was concluded that Optixcell® extender allowed better cryoprotection to Beni Arouss buck spermatozoa as showed by semen quality parameters.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)